The Inhibitory Effect of Epigallocatechin Gallate on the Viability of T Lymphoblastic Leukemia Cells is Associated with Increase of Caspase-3 Level and Fas Expression - Ghasemi-Pirbaluti, Masome (Indian J Hematol Blood Transfus, 2017)
Acute lymphoblastic leukemia is the most prevalent cancer in children. Novel components to help struggle aggressive malignancies and overcome some side effects of conventional treatments could be a promising strategy. Epigallocatechingallate (EGCG), have attracted the attention of scientists for prevention or treatment of some cancers. Jurkat cells were incubated with the different concentrations of EGCG (30–100 µm) for 24, 48, and 72 h and cell viability was investigated using MTS test. Apoptosis and the level of caspase 3 alterations were evaluated using flowcytometry and expression of Fas by Real Time PCR. EGCG decreased viability of cells with an inhibition concentration (IC50) of 82.8 ± 3.1, 68.8 ± 4 and 59.7 ± 4.8 μM in 24,48 and 72 h. 50, 70 and 100 µM concentrations of EGCG induced apoptosis in about 31, 40 and 71% of the cells, respectively. The mean value of caspase 3 positive cells in the presence of 50, 70 and 100 µm concentrations of EGCG was 19.3 ± 2.9, 29.5 ± 3.1 and 61.2 ± 3.4 respectively compared to 7.8 ± 1.1 in control with a significant difference at 100 µm concentration. Treatment with EGCG for 48 h enhanced the expression of Fas reaching to a significant level at 100 µM concentration. EGCG is effective in decrease cell viability, apoptosis induction and enhancement of caspase 3 and Fas expression level in jurkat cells. A comprehensive understanding of molecular events and pharmacokinetics of the component and experiments in animal models are required for dose determination and its interaction with other components of combination chemotherapy.